If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + 6x = 136 Reorder the terms: 5(3 + x) + 6x = 136 (3 * 5 + x * 5) + 6x = 136 (15 + 5x) + 6x = 136 Combine like terms: 5x + 6x = 11x 15 + 11x = 136 Solving 15 + 11x = 136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 11x = 136 + -15 Combine like terms: 15 + -15 = 0 0 + 11x = 136 + -15 11x = 136 + -15 Combine like terms: 136 + -15 = 121 11x = 121 Divide each side by '11'. x = 11 Simplifying x = 11
| -2x-(3)=12+(x) | | 4m+12=112 | | 20a+14b+2c+5c-4b-2a= | | 0.12x+0.02x=50000 | | 7+7(x)=8+6(x) | | a+5*2=9 | | 3m+12=112 | | 11x=6x-15 | | 4x^2-2x=6x^2-2(x^2-x) | | x^4+7x^3+11x^2-7x-12=0 | | 9x+2x-4x=28 | | 19.95+.99m+65.32=144.67 | | 10x+5=2x+45 | | 20q^2-9qr-18r^2= | | 10-4p+35=2-p | | 15p+17q+p-7q-4p= | | -0.04x-x-0.2x=6.2 | | 8-16w=-8(1+2w) | | 8x+2=x-3 | | 4x-9+3x-5+x=7x+2 | | 0.6666667x+6=0.5x+0.25x | | g(h)=-x^2+x-6 | | x^2+y^2-4x-6y+8=0 | | a-3b-2a= | | 25x-30=10x | | x^2+y^2-4x+6y+8=0 | | -10-(-2)= | | 143-2x=43x+18 | | 2.3x-5.4=-10 | | 7(x-3)-4x=-16 | | (x+1)=0 | | (2x+9)=x-3 |